2000
DOI: 10.1109/27.842910
|View full text |Cite
|
Sign up to set email alerts
|

The primary physico-chemical mechanism for the beneficial biological/medical effects of negative air ions

Abstract: The primary chemical mechanism of the beneficial medical/biological action of negative air ions necessary for life was studied. Air ion deficiency is the cause of many illnesses and treatment with air ion inhalation is effective in many cases. However, its application is limited by the absence of knowledge of the primary mechanism of its action. The superoxide anion O 2 was detected in the flow of negative air ions generated by an electroeffluvial air ionizer. Earlier, the appearance of hydrogen peroxide in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 18 publications
(10 reference statements)
0
25
0
1
Order By: Relevance
“…Evidence for the generation of superoxide during negative air ionization is given by several authors [25], [66], [67]. Its generation in the corona discharge was suggested by the protection conferred by the enzyme SOD to bacteria exposed to negative corona [25].…”
Section: Chemistry Of Electric Dischargesmentioning
confidence: 97%
See 1 more Smart Citation
“…Evidence for the generation of superoxide during negative air ionization is given by several authors [25], [66], [67]. Its generation in the corona discharge was suggested by the protection conferred by the enzyme SOD to bacteria exposed to negative corona [25].…”
Section: Chemistry Of Electric Dischargesmentioning
confidence: 97%
“…Exposing the bacteria Staphylococcus albus in solution to the products of a negative corona, with an estimated generation rate of 0.3 mmol O 2 • − per hour, substantial loss of viability was observed after 2 h and total loss seen after 5 h. Addition of SOD provided complete protection from the corona treatment such that total viability was retained, suggesting the superoxide radical to be largely responsible for bacterial death. The accumulation of O 2 • − in a solution treated with an electroeffluvial ionizer was also measured using electron paramagnetic resonance and found to be in the region of 0.5−1.0 µm/min [67].…”
Section: Chemistry Of Electric Dischargesmentioning
confidence: 99%
“…The typical lifetime of NAIs in clean air is approximately 100 s (Parts & Luts (2004); Daniels, 2002). Kondrashova et al (2000) indicated the beneficial biological effects of NAIs. Furthermore, studies have investigated the application of NAIs in hypertension therapy and the role of NAIs in promoting recovery from stress-and exercise-based injuries (Kondrashova et al, 2000;Ryushi et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…In a number of medical research projects, reported for example in [15]- [19], it has been proved that light negative ions have a positive effect on human health and their lack results in fatigue, health problems, and reduced performance at work. For example, special ionizers were tested that employ the stimulation of plants placed in a salt solution with high electric voltage [20], and their influence and effect on the tracheas of laboratory (sewer-) rats were evaluated, together with an analysis of the state of their blood.…”
Section: Introductionmentioning
confidence: 99%